Pemanfaatan Ekstrak Daun Jambu Biji (Psidium guajava Linn) Sebagai Antibakteri dan Antifungi - Nuryani, Siti (Jurnal Teknologi Laboratorium, 2017)
Guava (Psidium guajava Linn) is found throughout Indonesia. The leaves contain tannins that can be used as antibacterial and antifungal. The aims of this research are to determine the antiseptic power of guava leaf as antifungal and antibacterial.This research is pre experiments research with laboratory test to determine the inhibitory power of guava ethanol extract as anti-bacterial and anti-fungal. Guava leaves are old made 70% ethanol extract in LPPT UGM using maceration method. The extract made 3 concentrations ie 25%, 50% and 75%. Each concentration was tested for inhibitory by knowing the diameter of growth barrier to Candida albicans and Staphylococcus aureus. Each concentration is repeated 5 times, resulting in 15 data. The data were analyzed descriptively to illustrate their potential comparisons with chlorhexidine as standard materials. The extract of guava leaf using ethanol 70% in laboratory test resulted in average inhibitory zone diameter as follows: for mushroom C.albicans with extract 25%, 50%, and 75% were 13.4mm, 17.6mm, and 19.4mm. While for S. aureus is 2.2mm, 25.6mm, and 27.2mm. The effect of antifungal power of guava leaf extract (Psidium guajava Linn.) on the growth of Candida albicans fungus is smaller compared to Staphylococcus aureus bacteria